PENGARUH PENDIDIKAN TERHADAP PENDAPATAN DOMESTIK REGIONAL BRUTO DI INDONESIA - M. Nur Rianto Al Arif (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2014)
The aim of this research is to analyze the influence of education on gross domestic regional product at 33 provinces in Indonesia. The analysis method that used in this research is multiple regressions with six independent variables such as literacy rate, years of school, enrolment rate 1, enrolment rate 2, enrolment rate 3, and population. The result shown that years of school and population had an influence on gross domestic regional product in Indonesia, and literacy rate, enrolment rate 1, enrolment rate 2, and enrolment rate 3 didn’t have an influence of gross domestic regional product. From this result we can conclude that overall education had an impact on growth in IndonesiaDOI: 10.15408/sjie.v3i1.2062